2023
DOI: 10.17275/per.23.30.10.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Web-Based Collaborative Learning Method with Scratch on Critical Thinking Skills of 5th Grade Students

Abstract: This study aimed to investigate the effect of web-based collaborative learning method with Scratch software on the critical thinking skills of 5th grade students and to create materials in Scratch software on the biodiversity subject. This study, in which a quasi-experimental design with pre-test - post-test control group was used, was carried out with 96 fifth grade students selected using convenient sampling method. In the implementation of the study, in addition to the education and training activities on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…This study suggests that the CC learning model can serve as a viable alternative for enhancing students' creative thinking skills (Malik et al, 2023). Additionally, (Alp & Bulunuz, 2023) found that web-based collaborative learning utilizing Scratch software is effective in improving students' critical thinking skills. The results indicate that the group utilizing this method exhibited higher critical thinking skills compared to the group undergoing conventional learning approaches, suggesting a positive impact of integrating Scratch software into the learning process.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…This study suggests that the CC learning model can serve as a viable alternative for enhancing students' creative thinking skills (Malik et al, 2023). Additionally, (Alp & Bulunuz, 2023) found that web-based collaborative learning utilizing Scratch software is effective in improving students' critical thinking skills. The results indicate that the group utilizing this method exhibited higher critical thinking skills compared to the group undergoing conventional learning approaches, suggesting a positive impact of integrating Scratch software into the learning process.…”
Section: Resultsmentioning
confidence: 72%
“…Collaborative Learning is more flexible and provides opportunities for learners to interact freely and help each other achieve shared learning goals. According to research (Alp & Bulunuz, 2023), The integration of Collaborative Learning in science subjects has the potential to enhance students' grasp of concepts and foster critical thinking skills. As defined by (Loes, 2022), Collaborative Learning is an instructional approach that incorporates online technology to facilitate collaboration among students in the learning process.…”
Section: Literature Review 21 Collaborative Learningmentioning
confidence: 99%